Comparative assessment of renewable sources for critical facilities of decentralized supply - Karpenko, Vasily; Starodub, Yuriy; Rudyk, Yuri; Kuts, Viktor; Zdeb, Volodymyr (Видавництво Львівської політехніки, 2023)
The concept of energy supply is widely discussed, but there is no consensus on ways of its provision. In the current research, we have provided an analysis of available combinations of renewable sources for decentralized energy supply. It is important for critical facilities on territorial society and district levels. The article considers the safety of the technical component of a complex organizational and technical system by studying the functional relationship between the parameters: temperature, time, active power, hydrogen participation, etc. The idea of the work is to evaluate the ratios of generating capacities of different types of renewable sources in complex systems and select highly efficient technologies and energy means for decentralized energy supply.
Keywords: validation; deep well; geothermal energy; critical facility; energy supply